2009
DOI: 10.1194/jlr.m900037-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

LXR ligand lowers LDL cholesterol in primates, is lipid neutral in hamster, and reduces atherosclerosis in mouse

Abstract: This article is available online at http://www.jlr.org Supplementary key words cynomolgus monkey • dyslipidemia • fi broblast growth factor 19 • hypertriglyceridemiaAtherosclerosis is the major cause of cardiovascular disease and its incidence is on the rise due to its tight relationship to obesity and diabetes. Therapeutic interventions targeted at reducing elevated plasma low-density lipoprotein cholesterol (LDLc), the primary risk factor for development of atherosclerosis, do not eliminate cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 40 publications
1
76
0
1
Order By: Relevance
“…8A ). The effects of GW3965 on serum triglycerides have been previously reported in hamsters ( 40,41 ) and other rodent models ( 42 ).…”
Section: Effects Of Diet and Lxr Ligand Activation On Serum And Hepatmentioning
confidence: 99%
“…8A ). The effects of GW3965 on serum triglycerides have been previously reported in hamsters ( 40,41 ) and other rodent models ( 42 ).…”
Section: Effects Of Diet and Lxr Ligand Activation On Serum And Hepatmentioning
confidence: 99%
“…Hong et al suggested that LXR agonist raises plasma LDL cholesterol levels in primates, but not in mice, through activation of the LXR-regulated E3 ubiquitin axis. Another study from Quinet et al found that LXR ligand activation with the selective LXR agonist WAY-252623 lowers serum LDL cholesterol in cynomolgus monkeys, is neutral in Syrian hamsters, and reduces atherosclerosis in mouse (44). These results would question the relevance of ongoing efforts to target LXR in human diseases using rodent models.…”
Section: Lxr Function In Liver Lxr In Cholesterol Homeostasismentioning
confidence: 76%
“…Previous studies have shown increased VLDL-TG production or have provided circumstantial evidence for enhanced VLDL-TG clearance on LXR activation (4,14), whereas conflicting effects on circulating TG levels have been reported (4,11,(13)(14)(15). Application of ADAPT resolved this apparent inconsistency, as it revealed that VLDL-TG secretion predominates during the early response to LXR agonism, thereby initially invoking elevated VLDL-TG concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…Published data on the effects of pharmacologic LXR agonism on plasma VLDL-TG levels indicate transient effects in rodents and nonhuman primates (4,11,(13)(14)(15). The mechanistic basis of these temporal changes in plasma TG levels is currently unknown.…”
Section: Introductionmentioning
confidence: 99%